Caractérisation de la consommation domestique d’eau potable dans le temps et dans l’espace (Gironde, France) - Sandrine Gombert-Courvoisier; Bénédicte Rulleau; Patrick Eisenbeis (VertigO, 2024)
Domestic use accounts for 70-80 % of drinking water consumption. The French reference value of 120 m3/water subscriber/year does not take into account the distribution of water uses at home, nor their spatial and temporal distribution. A survey of 1026 residents of Gironde was conducted to characterise domestic drinking water consumption, and the volume of water per use was estimated. The results show that only a small share of this consumption is transferred to other locations (work, leisure) or other territories. Compared with the CIEau results, the volumes for personal care and watering are high, whereas the proportions for laundry, washing up and food are low, which can be explained by a difference in assumptions (time of presence, flow rates, duration, et cetera). In the context of water resource management, this update of domestic consumption should enable to target water savings more effectively.